Hardening a soft budget constraint through upward devolution to a supranational institution: The case of Italian state-owned firms and the European Union - Elisabetta Bertero; Laura Rondi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper contributes to the literature on the role of decentralization in hardening the budget constraint of public enterprises. Following Qian and Roland the study adopts a `federalist' approach. However, it interprets federalism as the upward devolution of domestic economic policies to a supranational authority and examines its role in disciplining public enterprises operating in a soft budget regime. The methodology is a case study of the shift in budget regime in Italy in the late 1980s. The study shows that a determinant role in driving this shift was played by European economic policies. The discipline imposed by participation in the EMS, the Single Market Programme and, later, the requirements to enter the EMU pushed the Italian government toward a much tougher approach to its budget deficit. The case study identifies a macroeconomic and a microeconomic channel through which the supranational institution—the European Commission—pressurised both the Italian government and the state-held corporate sector. It analyses the effects of the upward devolution on the hardening of the budget constraint of Italian public enterprises and provides empirical evidence of their restructuring and improved performance. Finally, the study extends the lessons from the case study to other countries and supranational institutions by examining two questions. First, to what other contexts the upward devolution of economic policies may be applied. Second, why supranational pressure might work where domestic reforms prove ineffective.
Keywords: E62; G28; L32; H32; H61; O19; 330; public enterprises; soft budget constraint; state aid; European integration; Italy; federalism; Öffentliches Unternehmen; Budgetrestriktion; Europäische Integration; Italien